Analyzing psychological conditions of field-workers in the construction industry. (2nd October 2017) - Lim, Soram; Chi, Seokho; Lee, Joon Deuk; Lee, Hoon-Jin; Choi, Hyunjung
ABSTRACT: The Korean construction industry has experienced poor labor productivity and high accident rates. Previous studies have reported that workers' mental health can cause negative impacts on work performance; thus, enhancing workers' psychological conditions would help achieve more productive and safer workplaces. This research aimed to understand the level of psychological conditions of construction field-workers using four categories: (1) stress (occupational stress and stress-coping style), (2) personal temperament, (3) emotional disturbance (depression and trait anxiety), and (4) drinking habits. This research used validated questionnaires commonly used in the field of clinical psychology, surveyed 430 respondents from road, bridge, tunnel, subway, and apartment construction sites in Korea, and analyzed the overall psychological tendency of construction workers with the collaboration of professional clinical psychologists using the Z-test, analysis of variance (ANOVA), and cross-tabulation. The research also investigated how the mental conditions differed according to different working conditions, such as demographic information, employment status, work types, work experience, and wage conditions. The results indicated that construction workers suffer from a high level of stress and showed high inclination for problem-focused coping: impulsive, cautious, and dependent on other people. Two out of five construction workers suffer from depression and experience trait anxiety. More seriously, three out of five workers show alcohol-use problems that require clinical attention. This study also revealed the particular psychological problems that occur under different working conditions. The findings can be used to promote the awareness of the importance of construction workers' mental well-being and to help in setting targets for improvement.